A class of Julia exceptional functions - Khoroshchak, V.S.; Khrystiyanyn, A.Ya.; Lukivska, D.V. (Carpathian Mathematical Publications, 2016)
The class of $p$-loxodromic functions (meromorphic functions, satisfying the condition $f(qz) = pf(z)$ for some $q \in \mathbb{C}\backslash \{0\}$ and all $z \in \mathbb{C}\backslash \{0\}$) is studied. Each $p$-loxodromic function is Julia exceptional. The representation of these functions as well as their zero and pole distribution are investigated.